European Society of Cardiology quality indicators for the prevention and management of cancer therapy-related cardiovascular toxicity in cancer treatment - Lee, G A; Aktaa, S; Baker, E; Gale, C P; Yaseen, Israa F; Gulati, G; Asteggiano, R; Szmit, S; Cohen-Solal, A; Abdin, A; Jurczak, W; Garrido Lopez, P; et al. (European heart journal. Quality of care & clinical outcomes, 2022)
AIMS: To develop quality indicators (QIs) for the evaluation of the prevention and management of cancer therapy-related cardiovascular toxicity. METHODS AND RESULTS: We followed the European Society of Cardiology (ESC) methodology for QI development which comprises (i) identifying the key domains of care for the prevention and management of cancer therapy-related cardiovascular toxicity in patients on cancer treatment, (ii) performing a systematic review of the literature to develop candidate QIs, and (iii) selecting of the final set of QIs using a modified Delphi process. Work was undertaken in parallel with the writing of the 2022 ESC Guidelines on Cardio-Oncology and in collaboration with the European Haematology Association, the European Society for Therapeutic Radiology and Oncology and the International Cardio-Oncology Society. In total, 5 main and 9 secondary QIs were selected across five domains of care: (i) Structural framework, (ii) Baseline cardiovascular risk assessment, (iii) Cancer therapy related cardiovascular toxicity, (iv) Predictors of outcomes, and (v) Monitoring of cardiovascular complications during cancer therapy. CONCLUSION: We present the ESC Cardio-Oncology QIs with their development process and provide an overview of the scientific rationale for their selection. These indicators are aimed at quantifying and improving the adherence to guideline-recommended clinical practice and improving patient outcomes.
Keywords: Neoplasms; nádory; lékařská onkologie; Cardio-oncology; Assessment; Quality indicators; Quality Indicators, Health Care; lidé; Cancer therapy-related cardiovascular toxicity; ukazatele kvality zdravotní péče; Treatment; Medical Oncology; Outcomes; kardiologie; Cardiology; Humans